Adolescent stress induces behavioral changes and hippocampal excitatory/inhibitory imbalance: involvement of redox dysregulation and mitochondrial dysfunction - Silva, Thamyris Santos (2023)
The developing adolescent brain is highly susceptible to social experiences and environmental insults, influencing how personality traits emerge. We previously found that adolescent stress leads to long-lasting behavioral changes and excitatory/inhibitory (E/I) balance dysregulation in the ventral hippocampus (vHip) associated with neurodevelopmental disorders, such as schizophrenia and bipolar disorder. The neurobiological mechanisms of psychiatric disorders have been linked with oxidative damage and reduced antioxidant capacity in the brain. However, the impact of severe stressors during adolescence, a critical neurodevelopmental period, on mitochondrial function, redox balance, and their functional consequences are not completely understood. We hypothesized that mitochondrial respiratory function and redox homeostasis in the vHip are affected by adolescent stress, leading to behavioral and electrophysiological changes associated with neuropsychiatric disorders. First, we performed a behavioral characterization during late adolescence (postnatal day, PND 47 - 50), including naïve animals and animals exposed to stress from PND 31 until 40 (10 days of footshock and 3 restraint sessions) by assessing sociability (social interaction test) and cognition function (novel-object recognition test). Then, we uncovered changes in E/I balance by analyzing the activity of glutamate pyramidal neurons, and the number of parvalbumin (PV)-containing GABAergic interneurons and their possible association with oxidative stress. To address the dynamic impact of stress on mitochondrial redox homeostasis, we performed high-resolution respirometry, DHE staining, MitoSox™ and AmplexRed® assays one (PND 41) and ten days (PND 51) after stress protocol. Also, we evaluated glutathione (GSH) and glutathione disulfide (GSSG) levels at PND 51. Finally, we assess the genome-wide transcriptomic signature of vHip of stressed animals by performing a bulk RNAsequencing following the behavioral tests. One week after stress, adolescent-stressed animals exhibited: (1) loss of sociability and cognitive impairment; (2) enhanced vHip pyramidal neuron activity; and (3) reduction in the number of PV-positive cells and their associated perineuronal nets. These changes were associated with an increased marker of oxidative stress in the vHip, in which was co-localized with PV interneurons. By performing high-resolution respirometry analysis, we found that stress impacted mitochondrial uncoupled efficiency (PND 41) and the phosphorylation capacity (PND 51). In addition, stressed animals displayed long-lasting redox dysregulation in the vHip, as revealed by molecular analysis. GSSG levels were increased in the vHip and serum of stressed animals and negatively correlated with social and cognitive performance, indicating that GSH was previously oxidized by ROS in stress conditions, and may affect behavioral phenotype. In another cohort of animals, we identified three cluster subgroups by performing principal component analysis of behavioral assessment: naïve higher-behavioral z-score (HBZ), naïve lower-behavioral z-score (LBZ), and stressed animals. Genes encoding subunits of oxidative phosphorylation complexes were significantly down-regulated in both naïve LBZ (Cox7c) and stressed animals (Coa5), while the Txnip gene that encoded thioredoxin-interacting protein were up-regulated in stressed animals and negatively correlated with behavioral performance. Our results identify mitochondrial genes associated with distinct adolescent behavioral phenotypes and highlight the negative impact of adolescent stress on vHip mitochondrial respiratory function and redox regulation, in which are partially associated with E/I imbalance and behavioral abnormalities.